Elaboration of PCBM Coated P3HT Nanoparticles: Understanding the Shell Formation - Palacio Valera, Abigail; Schatz, Christophe; Ibarboure, Emmanuel; Kubo, Takaya; Segawa, Hiroshi; Chambon, Sylvain (Frontiers in Energy Research, 2019)
Solvent displacement, or nanoprecipitation, is a well-known process to develop colloidal dispersions in water. Using two successive and selective nanoprecipitation steps, we developed a method to generate [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) shell on poly(3-hexylthiophene) (P3HT) core nanoparticles (P3HT@PCBM). We report herein on the understanding of the shell formation during this process. Using several techniques (dynamic light scattering, zeta-potential, photoluminescence), we evidenced that after the first solvent displacement with dimethyl sulfoxide (DMSO), the PCBM molecules still dissolved in the medium are already in close interaction with the P3HT nanoparticles (NP). Such proximity of the P3HT core with PCBM molecules in the DMSO dispersion explains why PCBM aggregates around the nanoparticles during the second solvent displacement with water. A fast electron transfer from P3HT to PCBM was identified by transient absorption spectroscopy, confirming the core-shell morphology even for low PCBM concentration. This study opens the route for the development of well-defined nano-objects dispersed in water for fabrication of organic photovoltaic devices with eco-friendly processes.